The war of Jenkins' ear - "Morpurgo, Michael" (London; Egmont, 2017)
SCHOOL STORIES. Michael Morpurgo is a master storyteller, former Children's Laureate and multi-award winner. This is a fresh reissue of a much-loved story with a beautiful new cover. Toby Jenkins hates going to Redlands' Boarding School - he gets called 'Jinks' and thinks he'll never make the top rugby team. But then, he meets Christopher who claims to have powers. Christopher promises Toby a miracle. When Toby goes fishing he crosses to the other side even though he knows it belongs to the villagers. The village boys catch Toby and beat him up, injuring his ear. Thus, the war of Jenkins' ear begins with all-out sticks and stones battles. Will Christopher be able to provide a much-needed miracle? Ages 9+
Donated by "Book Planet", Dated 18-4-2025.
Keywords: Friendship-English fiction